A BRIEF REPORT: INCORPORATING SALUTOGENIC PRACTICES IN EFFECTIVE MENTORSHIP FOR STUDENT WELLNESS - Sethuraman K.R. (Asian Journal of Medicine & Health Sciences, 2019)
Generations of medical students have been told of the celebrated quote of Sir William Osler, “As is our pathology, so is our practice”. 1 Those who are aware of salutogenic principles and have adopted them in their own life may paraphrase that quote to say, “As is our salutogenesis, so is our wellbeing.” Even though the WHO has defined health as "a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity", with so much of stress on learning pathogenesis and pathology during their studies, most medical professionals are not aware of salutogenic principles, which focus on promoting wellness.